A game-theory based Multi-plant Collaboration Model (MCM) for cross-plant prevention in a chemical cluster - Reniers, Genserik; Cuypers, Senne; Pavlova, Yulia (Elsevier, 2012)
The presented Multi-plant Collaboration Model uses game theory to evaluate different strategic crossplant precaution collaboration situations. The model first assumes prevention management s perceptions as a premise to take cross-plant prevention decisions. Second, it employs information from the different plants and aggregates the data to determine possible financial collaboration benefits within the entire industrial area. By doing so, an application of the model by a suggested independent supra-plant council may enhance and realize cross-corporation precaution in chemical clusters.
Keywords: MA; game-theory; Collaboration model; Chemical cluster; Prevention management; kemianteollisuus; turvallisuus; peliteoria